Peran Financial Distress Risk dan Firm Size Sebagai Variabel Moderasi Pada Pengaruh Financial Leverage Terhadap Financial Performance - Malinda Amelia Kusuma; Hersugondo Hersugondo (Jurnal Akuntansi dan Pajak, 2023)
Capital structure decisions are the most important decisions affecting company performance as well as shareholder value. Companies need to understand aspects of the costs and benefits of debt in determining a capital structure that can maximize performance. Financial distress risk and firm size are controversial issues in choosing a capital structure that can affect the relationship between leverage and financial performance. Researchers tested the role of financial distress risk and firm size as moderating variables on the effect of financial leverage on financial performance. Quantitative research techniques and secondary data sources are time series. Researchers obtained data through financial statements of companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The population of 834 companies was selected based on the criteria so that the sample in this study was 116 companies (580 units of observation). The research method uses descriptive statistical tests, classical assumption tests, and regression tests (multiple linear regression tests and moderated regression tests). The results of this study indicate that the first hypothesis, financial leverage has a significant negative impact on financial performance (ROA and ROE). The second hypothesis is that financial distress risk can moderate (strengthen) the negative impact between financial leverage and financial performance (ROA and ROE). The third hypothesis shows that firm size does not moderate the effect of financial leverage on financial performance (ROA) and firm size moderates (strengthens) the effect of financial leverage on financial performance (ROE). Keywords : Financial Performance, Financial Leverage, Financial Distress Risk, Firm Size